O161 LASTING SYMPTOMS AFTER ESOPHAGEAL RESECTION (LASER) – EUROPEAN MULTI-CENTER CROSS-SECTIONAL STUDY. (23rd November 2019) - Markar, S; Zaninotto, G; Castoro, C; Johar, A; Lagergren, P; Elliott, J; Gisbertz, S; Mariette, C; Alferi, R; Huddy, J; Sounderajah, V; Pinto, E; et al.
Abstract: Aim: Long-term functional outcomes and the associations to health-related quality of life (HRQOL) after esophagectomy is largely unknown. LASER is a multi-center European study aimed to identify the most prevalent symptoms, and those with the greatest impact upon HRQOL among patients surviving more than one-year after esophagectomy for cancer, and to develop a clinically relevant symptom-based tool to measure HRQOL. Background & Methods: Between 2010 and 2016, patients from 20 European Centers who underwent esophagectomy for esophageal cancer, and were disease-free at least one year postoperatively were invited to complete the LASER questionnaire, EORTC-QLQ30 and OG25. Specific symptom questionnaire items that were associated with a poor HRQOL as identified by EORTC-QLQC30 and OG25 were identified by multivariable linear and logistic regression analysis and combined to form a tool, which was tested using receiver operating characteristics curve analysis. Results: A total of 876 of 1081 invited patients responded to the questionnaire, giving a response rate of 81%. Of these, 66.9% stated in the last 6 months they had had symptoms associated with their esophagectomy and 52.4% of patients had sought medical treatment for their symptoms. Ongoing weight loss was reported by 10.4% of patients while 32.4% were struggling to maintain their body weight, and 18.8% of patients required supplemental oral nutrition. Only 13.8% of patients had returned to work with the same activities as before. Three LASER symptoms in multivariate analysis were correlated with poor HRQOL; pain on scars on chest (Odds ratio (OR) 1.27; 95% CI 0.97-1.65), low mood (OR 1.42; 95% CI 1.15-1.77) and reduced energy or activity tolerance (OR 1.37; 95% CI 1.18-1.59). The areas under the curves for the development and validation datasets were 0.81±0.02 and 0.82±0.09 respectively. Conclusions: Two-thirds of patients experience symptoms related to their esophagectomy more than one year after surgery. The three key symptoms associated with poor HRQOL identified in this study should be further validated, and could be used in clinical practice to identify patients who require increased long-term term support.